Developmental stratification of the mammary epithelium occurs through symmetry-breaking vertical divisions of apically positioned luminal cells - Huebner, Robert J. (Company of Biologists, 2014)
Mammary ducts are elongated during development by stratified epithelial structures, known as terminal end buds (TEBs). TEBs exhibit reduced apicobasal polarity and extensive proliferation. A major unanswered question concerns the mechanism by which the simple ductal epithelium stratifies during TEB formation. We sought to elucidate this mechanism using real-time imaging of growth factor-induced stratification in 3D cultures of mouse primary epithelial organoids. We hypothesized that stratification could result from vertical divisions in either the apically positioned luminal epithelial cells or the basally positioned myoepithelial cells. Stratification initiated exclusively from vertical apical cell divisions, both in 3D culture and in vivo. During vertical apical divisions, only the mother cell retained tight junctions and segregated apical membranes. Vertical daughter cells initiated an unpolarized cell population located between the luminal and myoepithelial cells, similar to the unpolarized body cells in the TEB. As stratification and loss of apicobasal polarity are early hallmarks of cancer, we next determined the cellular mechanism of oncogenic stratification. Expression of activated ERBB2 induced neoplastic stratification through analogous vertical divisions of apically positioned luminal epithelial cells. However, ERBB2-induced stratification was accompanied by tissue overgrowth and acute loss of both tight junctions and apical polarity. Expression of phosphomimetic MEK (MEK1DD), a major ERBB2 effector, also induced stratification through vertical apical cell divisions. However, MEK1DD-expressing organoids exhibited normal levels of growth and retained apicobasal polarity. We conclude that both normal and neoplastic stratification are accomplished through receptor tyrosine kinase signaling dependent vertical cell divisions within the luminal epithelial cell layer.